2021
DOI: 10.1016/j.rbmo.2020.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal changes in follicle distribution in the human ovarian cortex

Abstract: Research question: How does follicle distribution evolve in the human ovarian cortex between the ages of 20 and 35? Design: Fragments of ovarian cortex from women who underwent unilateral oophorectomy for fertility preservation were obtained for quantitative histological assessment, including recording of the two-dimensional coordinates of follicles. Data were analysed using spatial statistical methods. Results:From 14 patients aged 20-35 years, 53 ovarian cortex tissue samples were obtained, containing 1-803 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Beyond its potential involvement in controlling follicle initiation of growth as discussed above, it has been suggested that ovarian follicles follow this rigidity gradient to accommodate their growth, migrating inward from the dense cortex towards the more pliant medulla and eventually back to the ovarian periphery for ovulation ( Woodruff and Shea, 2011 ). Our spatial analysis of follicle localization shows that follicles are not uniformly distributed within the cortex, in agreement with several previous reports ( Schmidt et al , 2003 ; Schenck et al , 2021 ), but rather are concentrated in the mid-cortical region, where the ECM is more flexible. Moreover, it confirms that follicular growth follows a geographically determined pattern, moving towards the medulla side as folliculogenesis progresses and the ovarian cortex undergoes active remodelling.…”
Section: Discussionsupporting
confidence: 92%
“…Beyond its potential involvement in controlling follicle initiation of growth as discussed above, it has been suggested that ovarian follicles follow this rigidity gradient to accommodate their growth, migrating inward from the dense cortex towards the more pliant medulla and eventually back to the ovarian periphery for ovulation ( Woodruff and Shea, 2011 ). Our spatial analysis of follicle localization shows that follicles are not uniformly distributed within the cortex, in agreement with several previous reports ( Schmidt et al , 2003 ; Schenck et al , 2021 ), but rather are concentrated in the mid-cortical region, where the ECM is more flexible. Moreover, it confirms that follicular growth follows a geographically determined pattern, moving towards the medulla side as folliculogenesis progresses and the ovarian cortex undergoes active remodelling.…”
Section: Discussionsupporting
confidence: 92%
“…With advancing age, the density of primordial follicles in the ovarian cortex derived from autopsy or biopsy specimens declines and the spatial distribution of follicles becomes more clustered. 37,38 Indeed, a relation exists between size of the primordial follicle pool and menopausal age. 39 Assessment of primordial follicle density is impractical in an ordinary clinical setting, but several studies have related number of antral follicles (AFC) and ovarian volume to age at menopause.…”
Section: Morphometric Studiesmentioning
confidence: 99%
“…Considering clustering of preantral follicles using Morisita’s index of clustering, all areas of the mare ovary indicated clustering, regardless of mare age, ovarian portion, or ovarian region. Clustering of preantral follicles in the ovary has been documented in both mice [ 20 , 29 , 30 ] and women [ 20 , 31 ]. Interestingly, the aforementioned studies reported that follicular clustering increases with age in both species, perhaps due to expected decreases in follicle density and regular follicular activity over time [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clustering of preantral follicles in the ovary has been documented in both mice [ 20 , 29 , 30 ] and women [ 20 , 31 ]. Interestingly, the aforementioned studies reported that follicular clustering increases with age in both species, perhaps due to expected decreases in follicle density and regular follicular activity over time [ 31 ]. However, in the present study, it was found that clustering decreased with age, a finding that is supported by the fact that in old mares, the spatial distribution of follicles exhibits a more dispersive pattern [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation